Low‐grade fibromyxoid sarcoma arising within the median nerve. Issue 3 (3rd January 2018) - Swanson, Amy A.; Giannini, Caterina; Folpe, Andrew L.; Van Dyke, Daniel L.; Amrami, Kimberly K.; Michalak, William A.; Vaubel, Rachael A.
Abstract : We report a case of low‐grade fibromyxoid sarcoma arising within the median nerve. A 31‐year‐old woman presented with symptoms of carpal tunnel syndrome and an enlarging mass in her right palm over 1 year. MRI demonstrated a mass associated with the right median nerve with solid and cystic components. At surgery, the mass was located within the epineurium, could be bluntly dissected from the nerve fascicles, and was suspected to be a schwannoma. A 3.4 cm, tan‐pink, glistening, smooth, homogenous mass was submitted to pathology. Microscopically, the tumor was a solid and cystic circumscribed nodule with a dense fibrous pseudocapsule. The tumor cells were uniformly bland and spindle‐shaped, with small, hyperchromatic oval nuclei and were embedded in an alternating fibrous and myxoid stroma with a prominent curvilinear vasculature and perivascular sclerosis. The differential diagnosis for this lesion included myxoid neurofibroma, schwannoma, soft tissue perineurioma, low‐grade malignant peripheral nerve sheath tumor and low‐grade fibromyxoid sarcoma. The tumor cells expressed MUC4, GLUT‐1, and vimentin and were negative for S‐100 protein, epithelial membrane antigen, smooth muscle actin, desmin, claudin‐1, neurofilament and SOX10. Fluorescence in situ hybridization, with a break‐apart probe strategy, demonstrated FUS rearrangement, consistent in this morphological context with the low‐grade fibromyxoid sarcoma‐associated FUS‐CREB3L2 or FUS‐CREB3L1 fusions. Low‐grade fibromyxoid sarcoma is exceptionally rare in the peripheral nerve, with only a single previously reported case. Nonetheless, as our case illustrates, this entity must be included in the differential diagnosis of unusual intraneural mesenchymal tumors. As in all other locations, intraneural low‐grade fibromyxoid sarcomas should be excised with negative margins. Patients with this disease require long‐term clinical follow‐up, given this tumor's propensity for very late distant metastases to the lungs and other sites.